EVALUASI SISTEM PENGENDALIAN INTERN PENJUALAN JASA RAWAT INAP PADA RUMAH SAKIT DAERAH KOTA KENDARI - Pratiwi, Anugrah (JIEM : Journal Of International Entrepreneurship And Management, 2022)
This paper intent to Know Internal Control System Evaluation Service Sell Nurses Lodge on Kendari City Hospital, Data collecting is done by use of interview and documentation. The Result of this research that Internal control system elements service sell nurses lodge on Kendari City Hospital adequately is equal to. Logistic separation and authorization system that applying to reduce its happening possible glosses over or deceitfulness. Proof document authorization system nursed lodge which did by more than one function enables to happen check, so gotten by confidence is equal to that unit that is nursed was aptly accomplished its payment. Mark sense auditor internal and external enable fault or happening deceitfulness gets shortly acknowledged. Internal control examination result with level reliability 95% and level faults 5% point out effectiveness